Reflections on Sculptural Thinking in Fashion. (2nd January 2016) - Swindells, Steve; Almond, Kevin
Abstract: What does it mean to think sculpturally in fashion practice? This paper explores some of the philosophical and practical aspects of three-dimensional thinking in fashion design; it does this by engaging with theories, concepts and philosophies related to thought and the experience of creating three-dimensional artifacts, which are common to both sculpture and fashion. Central to this relationship is the employment of the senses with respect to perception and cognition. Of particular interest is the sense of touch, and how sensory experience encounters notions of empathy and mimicry in a phenomenological encounter with others: whether animate or inanimate. The research emerged through conversations between a fashion designer, Kevin Almond, and a contemporary artist, Stephen Swindells. The sensibility of the paper, and much of the analysis and debates, thus explore these issues from a creative practitioner's perspective. A conceptual current running through the conversation, and subsequently the paper, touched upon whether following a line of thought becomes analogous to visually and mentally tracing a human form in a psychological space—and what is the significance for fashion of the interrelationships between sculptural thinking and phenomenological encounters with others within urban environments.